Regards sur l'art américain des années soixante - Gintz, Claude; Bochner, Mel; Glaser, Bruce; Greenberg, Clement; Judd, Donald; Krauss, Rosalind E.; Morris, Robert; Pincus-Witten, Robert; Rose, Barbara; Steinberg, Leo (Paris : Galerie Durand-Dessert Paris, 1979)
Andre, Carl ; Artschwager, Richard ; Bochner, Mel ; Bontecou, Lee ; Chamberlain, John ; Diebenkorn, Richard ; Diller, Burgoyne ; Dubuffet, Jean ; Riverhead (New York) ; Francis, Sam ; Frankenthaler, Helen ; Gottlieb, Adolph ; Hofmann, Hans ; Johns, Jasper ; Judd, Donald ; Kelly, Ellsworth ; Kline, Franz ; de Kooning, Willem ; LeWitt, Sol ; Lichtenstein, Roy ; Louis, Morris ; Morris, Robert ; Motherwell, Robert ; Newman, Barnett ; Noland, Kenneth ; Oldenburg, Claes ; Olitski, Jules ; Pollock, Jackson ; Rauschenberg, Robert ; Rockburne, Dorothea ; Rothko, Mark ; Serra, Richard ; Stella, Frank ; Still, Clyfford ; Warhol, Andy
2 ex.
Frans
boek
Keywords: Verenigde Staten